2020
DOI: 10.1177/2158244020932536
|View full text |Cite
|
Sign up to set email alerts
|

Examining Students’ Responses to Teacher Translation Feedback: Insights From the Perspective of Student Engagement

Abstract: This case study investigated students’ response to feedback in the lens of student engagement with teacher feedback on their translation work. Drawing upon data from multiple sources, including students’ translation assignments, classroom observations, semi-structured interviews, stimulated recalls, and other documents, it explored how three Chinese undergraduates engaged with the feedback affectively, behaviorally, and cognitively. The findings reveal that (a) the students went through varying mood swings, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This finding agrees with Moonen (2015) and Y. Zheng et al (2020), who found that participants were enthusiastic and positive in the collaborative process using Google Docs to improve their final products. Similarly, B.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding agrees with Moonen (2015) and Y. Zheng et al (2020), who found that participants were enthusiastic and positive in the collaborative process using Google Docs to improve their final products. Similarly, B.…”
Section: Discussionsupporting
confidence: 90%
“…Kim (2013) asserts that few studies have tackled students' engagement cognitively in online platforms, while the majority focused on investigating students' behavioral interactions. Research tackling engagement has focused on investigating the relationship between students' behaviors and their academic achievement (Yu et al, 2018;Y. Zheng et al, 2020).…”
Section: Students' Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Pietrzak (2014) presented feedback circulation model within a group of translation students. Zheng, Zhong, Yu and Li (2020) examined the correlation between students' translation competency level and their engagement with the received teacher feedback. Finally yet importantly, Yu, Zhang, Zeng and Lin (2019) dealt with the teacher's strategies for written translation feedback generation and their impact upon students' revision.…”
Section: Literature Reviewmentioning
confidence: 99%